The efficacy of cognitive and behavior therapies for insomnia on daytime symptoms: A systematic review and network meta-analysis. (August 2020) - Benz, Fee; Knoop, Teresa; Ballesio, Andrea; Bacaro, Valeria; Johann, Anna F.; Rücker, Gerta; Feige, Bernd; Riemann, Dieter; Baglioni, Chiara
Abstract: Insomnia disorder, defined by nocturnal and daytime symptoms, is highly prevalent worldwide and is associated with the onset of mental illness. Although daytime symptoms are often the reason insomnia patients seek help, it is not clear whether recommended treatment is effective on daytime symptoms. We aimed to investigate the efficacy of cognitive and behavior therapies for insomnia (CBT–I) on all daytime symptoms explored in the literature using both direct and indirect data. 86 studies (15, 578 participants) met inclusion criteria. Results showed significant effects of CBT-I administered face-to-face individually, in group and different self-help settings on depressive symptoms, anxiety, daytime sleepiness, fatigue, quality of life, daytime and social functioning and mental state, with Cohen's d's ranging from −0.52 and 0.81. Our results suggest that CBT-I is effective in the treatment of daytime symptoms, albeit with predominantly small to moderate effects compared to far stronger effects on the core symptoms of insomnia. Effects may be biased for depressive and anxiety symptoms, since many included studies excluded patients with severe levels of these complaints. Further, small to moderate effects may reflect that CBT–I, by improving nighttime symptoms, has a positive effect on daytime symptoms, but it does not target the daytime symptoms directly. Future studies may benefit from adding therapeutic techniques that address daytime symptoms more directly. Highlights: Ten subgroups of daytime symptoms were identified in the literature. Cognitive and behavior therapies for insomnia are effective on daytime symptoms. Effects are predominantly small to moderate compared to stronger effects on nocturnal symptoms. CBT-I might benefit from adding techniques targeting more directly daytime symptoms.